Formulation of Functional Yogurt from Corn-Mung Bean Extract Blend Using Commercial Biokul Starter Culture (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Yogurt is a fermented dairy product containing Lactobacillus bulgaricus and Streptococcus thermophilus, known for its health benefits. This study aimed to evaluate the color quality, hedonic acceptance, and pH of yogurt formulated with a blend of corn extract and mung bean extract. The research was conducted at Politeknik Negeri Sriwijaya, Palembang, employing an experimental method involving: (1) preparation of corn and mung bean extracts, followed by (2) fermentation using commercial plain yogurt starter culture (Biokul brand). We compared: monocomponent (corn) versus composite (corn-mung bean) formulations. Results demonstrated significant color variation between single-extract (corn) and blended-extract yogurts. Hedonic testing revealed significantly higher consumer preference for the blended formulation compared to corn-only yogurt. pH analysis showed no statistically significant difference between the final pH values of both products. The study concludes that the optimal product formulation is the sweet corn-mung bean blended yogurt, based on superior organoleptic acceptance while maintaining equivalent acidity levels.